Elongated Hypocotyl 5-Homolog (HYH) Negatively Regulates Expression of the Ambient Temperature-Responsive MicroRNA Gene MIR169 - Serivichyaswat, Phanu T.; Susila, Hendry; Ahn, Ji Hoon (Frontiers in Plant Science, 2017)
Arabidopsis microRNA169 (miR169) is an ambient temperature-responsive microRNA that plays an important role in stress responses and the floral transition. However, the transcription factors that regulate the expression of MIR169 have remained unknown. In this study, we show that ELONGATED HYPOCOTYL 5-HOMOLOG (HYH) directly binds to the promoter of MIR169a and negatively regulates its expression. Absolute quantification identified MIR169a as the major locus producing miR169. GUS reporter assays revealed that the deletion of a 498-bp fragment (–1,505 to –1,007, relative to the major transcriptional start site) of MIR169a abolished its ambient temperature-responsive expression. DNA-affinity chromatography followed by liquid chromatography-mass spectrometry (LC-MS) analysis identified transcription factor HYH as a trans-acting factor that binds to the 498-bp promoter fragment of pri-miR169a. Electrophoretic mobility shift assays (EMSAs) and chromatin immunoprecipitation (ChIP)-quantitative PCR demonstrated that the HYH.2 protein, a predominant isoform of HYH, directly associated with a G-box-like motif in the 498-bp fragment of pri-miR169a. Higher enrichment of HYH.2 protein on the promoter region of MIR169a was seen at 23°C, consistent with the presence of more HYH.2 protein in the cell at the temperature. Transcript levels of pri-miR169a increased in hyh mutants and decreased in transgenic plants overexpressing HYH. Consistent with the negative regulation of MIR169a by HYH, the diurnal levels of HYH mRNA and pri-miR169a showed opposite patterns. Taken together, our results suggest that HYH is a transcription factor that binds to a G-box-like motif in the MIR169a promoter and negatively regulates ambient temperature-responsive expression of MIR169a at higher temperatures in Arabidopsis.